Los mensajes publicitarios de productos alimenticios de consumo masivo de las marcas mejores posicionadas de atún y su relación con las percepciones de calidad de vida de sus habitantes, aplicación en el Barrio Barrionuevo. - López Casa, Juan Gabriel (2013)
In Ecuador, most people analyze the great influence of advertising on their lives, both in the economic, social and cultural, stating that youth are the most affected in all that advertising provides, which leads us to determine that in the future, they will be influenced by one hundred percent is their purchasing decisions. This is why our research is based primarily on the influence of advertising messages on people and their relationship to perceptions of quality of life for consumers, so we have chosen to analyze specific neighborhood South Quito is the Barrrio Barrionuevo.